Some methodological aspects of animal behaviour during beef cattle grazing - Halász, András; Nagy, Géza (Acta Agraria Debreceniensis, 2012)
Ethology, the research field of animal behaviour, during the past half century developed into an independent science and became more important in recent years as the farming industry has turned toward quality production. Farm animals respond for every environmental factor. Essential to know the answers to avoid unpleasant economic consequences. Based on the shepherds’ experience, this science has merged with modern technology, constantly expanding and searching new methods. According to the literature the article summarizes the observation methods in cattle grazing. This paper introduces the beginnings and shows the future trends. Finally we share personal experiences as the Hungarian Grey cattle grazing behaviour at conditions of Hortobágy, Hungary.